Changes in myofibrillar structure of silver carp (Hypophthalmichthys molitrix) as affected by endogenous proteolysis under acidic condition. (7th September 2016) - Yang, Fang; Xia, Wenshui; Rustad, Turid; Xu, Yanshun; Jiang, Qixing
Summary: Effect of endogenous proteolysis on myofibrillar conformational changes under acidic condition was investigated by spectroscopic techniques. The result of intrinsic tryptophan fluorescence showed that tryptophan residues were exposed to polar environment by acid denaturation of protein and participation of endogenous proteolysis. Extrinsic fluorescence indicated that average surface hydrophobicity (Sh ANS) decreased by reduction of pH but increased by endogenous proteolysis. Second‐derivative UV‐spectroscopy implied that the decrease of Sh ANS under acidic condition may be due to burying of some aromatic amino acid residues into hydrophobic cores induced by acid‐induced aggregation, such as tyrosine, while Sh ANS increased by exposure of some hydrophobic amino acids due to the effect of endogenous proteases. Raman spectra verified the changes in microenvironment of tryptophan and tyrosine residues, and showed that aliphatic amino acids were mainly exposed to polar solvent by both acid denaturation and endogenous proteolysis. In addition, new disulphide bonds were less likely to form by acid‐induced aggregation and proteolytic cleavage, while random coils increased and smaller water domains were found. Abstract : Effect of acid and endogenous proteases on myofibrillar structural change of silver carp.